Efficacy of peroxygen disinfestants against non-fungal plant pathogens in agricultural and horticultural production: a systematic review and meta-analysis - Copes, Warren E.; Ojiambo, Peter S. (Frontiers in Horticulture, 2024)
A quantitative review was performed on the effectiveness of peroxygen products that contain hydrogen peroxide (HP), peracetic acid (PAA) and potassium peroxy-monosulfate (PPMS) to eliminate non-fungal plant pathogens in agricultural and horticultural cropping systems.This quantitative analysis is a complementary follow-up to a previous study on efficacy of peroxygen against fungal plant pathogens. The meta-analysis evaluated the biocidal activity of peroxygen intervention treatments against 15 different non-fungal plant pathogens in 81 studies compared to independent non-treated controls that were conducted over the last 30 years.The overall summary effect size was a Hedges' g ( g + ) of 1.98 for the random effects model, which indicates that peroxgen treatments caused a moderate to high reduction in viable propagules or disease progression in most cases. The range in efficacy was defined by the 95% prediction intervals (-0.82 to 4.80) and indicated peroxygen applications would range from ineffective to very highly effective in 95% of similar populations. Peroxygen compounds provided similar control (P = 0.5655) against bacteria, oomycetes and viruses, while being more effective against zygomycetes (P = 0.0001) than other organism types. Differences were observed between peroxygen active ingredients (a.i.) (P = 0.0203), where PPMS was more effective than HP + PAA. Differences were also observed when peroxygen compounds were applied on different target materials (P = 0.0004). Peroxygen compounds were moderately effective against non-fungal plant pathogens when applied in solution and on metal surfaces but ineffective when applied on plants under crop production conditions. Differences between target materials explained 50% of the true variances in a meta-regression model with the length of time peroxygens were in contact with target materials (P = 0.0416).Discussion: These results show that although the current recommended dose and contact time for commercial peroxygen products are expected to result in pathogen inactivation, their efficacy will likely be influenced by the organism and material being treated. This analysis serves as a base reference for considering efficacy performance of peroxygen compounds against non-fungal plant pathogens.